How do women comply with cancer screenings? A study in four regions of France - Nathalie Duchange; Marie Poiseuil; Quentin Rollet; Christine Piette; Mathilde Cosson; Marie-Christine Quertier; Grégoire Moutel; Sylviane Darquy (BMC, 2023)
Abstract Background This article looks at the behaviour of women facing different cancer screening options available to them from the age of 50 onward. The study was conducted in 2019 in four departments of the French territory with the objective of identifying the factors that influence acceptance of a population-based screening proposal. Methods A questionnaire was sent to women who had received three invitations to organised screenings (OS) for both breast and colorectal cancer. The categories of participants in both OS were designed from data from the regional cancer screening coordination centres in each department. Participation in opportunistic cervical cancer screening was evaluated as self-reported data. Results 4,634 questionnaires were returned out of the 17,194 sent, giving a global return rate of 27%. The highest rate of return (73.5%) was obtained from women who had participated at least once in both breast and colorectal cancer OS. An intermediate rate was obtained from women participating in breast cancer OS only (18.7%). Poor levels of return came from women who had participated in colorectal cancer OS only (3.6%) and from non-participants (4.1%). Our results suggest that women with lower educational levels tend to be the most regular attendants at OS (50.3%), compared to highly educated women (39.7%). 11.8% of women were overdue in their opportunistic cervical cancer screening. This percentage rose to 35.4% in the category of non-participants. In addition, women's comments provide a better understanding of the reasons for irregular attendance and non-participation. Conclusion Overall, similar behaviours towards screening were observed in the four departments. Our analysis suggests that participation in one cancer OS increases the likelihood of participating in others. This adhesion could be an interesting lever for raising women's awareness of other cancer screenings.